Potensi Interaksi Obat Pasien Penyakit Saraf di Rumah Sakit X Kabupaten Pidie Aceh: studi deskriptif kuantitatif - Lubis, Salmah Handayani; Hasanah, Fenny; Siahaan, Desy Natalia; Intan, Cut (Journal of Pharmaceutical and Sciences, 2026)
Background: Drug interactions can increase the risk of side effects and reduce the success of therapy, especially in neurological patients who often receive polypharmacy. Objective: This study aims to determine the effect of administering a combination of drugs as a trigger for potential drug interactions based on their classification (minor, moderate, major) in patients with neurological diseases. Methods: This study is a retrospective quantitative descriptive study with a cross-sectional design. The sample consisted of outpatient neurological patients who received more than two drugs that met the inclusion criteria. Potential drug interactions were analyzed using the https://www.drugs.com/drug_interactions.html. Results: The highest category of drug interactions was moderate (n= 52; 75%) with the following drug combinations: (amlodipine and bisoprolol); (Simvastatin + Miconazole); (Simvastatin + Omeprazole); (Hydrochlorothiazide + Codeine); (Codeine + Amitriptyline). In addition, a major drug interaction category (n=28; 25%) was found in the administration of drug combinations (simvastatin and amlodipine) causing liver damage; (Alprazolam + Codeine); (Diazepam + Codeine); (Codeine + Gabapentin) each of these three drug interactions can cause CNS depression, (Furosemide + Gentamicin) causes additive nephrotoxicity and ototoxicity. Conclusion: Moderate-category interactions were the most common (amlodipine and bisoprolol). These drug interactions included pharmacodynamic interactions, and the combination of these drugs could cause clinical risks (hypotension, bradycardia). These findings indicate the need for pharmacists to perform clinical pharmacy services related to prescription review and drug therapy monitoring for patients receiving more than two drugs, as well as providing information to patients on the appropriate timing and dosage of their medications to avoid moderate and major drug interactions in neurological patients in hospitals.